“Shaping the family”: Individual’s capabilities to exercise reproductive rights seen through a qualitative survey [“Dessiner sa famille”. Capabilités individuelles à exercer ses droits reproductifs à la lumière d’une enquête qualitative] - Sauvain-Dugerdil, C.; Bosiakoh, T.A.; Diarra, S.; Piraud, A.; Diop, S.; Anarfi, J.; Agyei-Mensah, S. (Etude de la Population Africaine, 2014)
We analyze here the outcome of focus group discussions and individual interviews conducted in Mali and Ghana. The aim is to identify collective images about family norms and emergence of alternative values, and to examine people’s degree of ambivalence towards norms and their ability to conceive and realize their own family plans. Discourses show that family life plans should not be seen as pre-established. Ability to shape the family appears conjectural both as regards current resources and the position in the family trajectory. In both countries, two types of resources play a key role: schooling and influence/support from the family and network. Results highlight that the least individual freedom is to be found at the start of family life and in gender power relationships; some freedom appears in the timing of fertility; while more room for individual agency characterizes youth and individuals with more personal resources and supportive surroundings. © 2014, Union for African Population Studies. All rights reserved.
Keywords: Ambivalence; Mali; Family norms; Family plans; Ghana; Qualitative survey